Correlation between echocardiographic left ventricular mass and atherogenic index of plasma in adult hypertensive subjects in Olabisi Onabanjo university teaching hospital, Sagamu - Oresegun, Olajide O.; Ogah, Okechuku S.; Familoni, Oluranti B.; Akinpelu, Akintunde (International Journal of Advances in Medicine, 2020)
Background: Hypertension and dyslipidaemia are two major modifiable cardiovascular risk factors with their co-existence having more than an additive effect on endothelial function causing atherosclerosis. The purpose of this study was to determine the prevalence of dyslipidaemia in hypertensive subjects and to determine its relationship left ventricular hypertrophy. Methods: The study was a cross-sectional comparative one involving 120 hypertensive participants with LVH (subjects) and 60 age and sex-matched hypertensive participants without LVH (controls). Detailed history, physical examination, fasting lipid profile test, and echocardiogram were carried out on all participants. Results: The overall prevalence rate of dyslipidaemia in the study was 61.1%. The prevalence of dyslipidaemia in subjects (60.8%) was slightly lower than in controls (61.7%), though the difference was not statistically significant (p=0.914). The most common isolated lipid abnormality in the study was elevated serum LDL-C (55% in subjects, 46.7% in controls), though the difference did not achieve statistical significance (p= 0.370). The mean atherogenic index of plasma (AIP) was significantly higher in the subjects (0.34+0.23) than in the controls (0.22+0.28) (p=0.001). There was a positive correlation between echocardiographic left ventricular mass and AIP (r=0.298, p=0.001). Conclusion: There is a high prevalence of dyslipidaemia among hypertensive adults. There is also a positive correlation between echocardiographic left ventricular mass and AIP among adult hypertensive subjects.